1993
DOI: 10.1139/v93-135
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of Wittig reactions with cyclic anhydrides. II.

Abstract: A study by NMR spectroscopic methods and trapping experiments of the mechanism of Wittig reactions between stabilized phosphoranes and unsymmetrically substituted cyclic anhydrides suggests that two reactions are involved: ( I ) a low-energy, reversible formation of acyclic adducts; and (2) a higher energy "Wittig olefination" reaction leading to enollactones. The latter, more selective, transformation requires a more highly organized transition state in which T-stacking and stabilizing complexations are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Later, during a mechanistic study of this reaction, it was found that in chloroform at room temperature the E isomer was formed in 52 % yield along with a 13 % yield of the Z isomer 20c. Non‐cyclic anhydrides are known to react with stabilized phosphoranes to afford the acylation products, diketo phosphoranes,21 and the occurrence of the normal Wittig reaction and the exclusive or predominant formation of the E isomers with phthalic anhydride were explained in terms of formation of a π–π complex between the C=O group of the phosphorane and the electron‐deficient benzenic ring of phthalic anhydride 20a,20c,20d. In the process of this investigation, when we realized that 3,6‐H atoms of phthalic anhydride and its analogues can form relatively strong HBs, we assumed that the H‐bonded complexes with the phosphorane can precede the Wittig reaction, and that chloroform, which is itself capable of H‐bonding, is therefore not the best choice as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Later, during a mechanistic study of this reaction, it was found that in chloroform at room temperature the E isomer was formed in 52 % yield along with a 13 % yield of the Z isomer 20c. Non‐cyclic anhydrides are known to react with stabilized phosphoranes to afford the acylation products, diketo phosphoranes,21 and the occurrence of the normal Wittig reaction and the exclusive or predominant formation of the E isomers with phthalic anhydride were explained in terms of formation of a π–π complex between the C=O group of the phosphorane and the electron‐deficient benzenic ring of phthalic anhydride 20a,20c,20d. In the process of this investigation, when we realized that 3,6‐H atoms of phthalic anhydride and its analogues can form relatively strong HBs, we assumed that the H‐bonded complexes with the phosphorane can precede the Wittig reaction, and that chloroform, which is itself capable of H‐bonding, is therefore not the best choice as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…This species is reasonably presumed to arise via tautomerization of the initial olefination product A to the thermodynamically more stable trisubstituted olefin. Although a few isolated cases of stabilized Wittig olefinations of lactones and esters have appeared in the literature, this condensation is an underutilized reaction in synthetic organic chemistry. Wittig reactions of stabilized ylides with the carbonyl groups of lactones, esters, thioesters, anhydrides, thioanhydrides, amides 17 and imides 18 have been reported in the literature, but many of these systems were intramolecular ring-closure reactions. Attempts to conduct the reaction at lower temperatures (in toluene or xylene at reflux) required longer reaction times and incomplete transformations with poor yields of 4 .…”
mentioning
confidence: 99%
“…Reacting phthalic anhydride ( 3a ) and thioloanhydride ( 4 ) with Wittig reagent 5 resulted in isomeric mixtures of the corresponding ( Z , Z )-, ( E , Z )-, and ( E , E )-products 6a and 7 (Scheme ). Interestingly, whereas only the synthetically useless isomers ( E , Z )- 6a and ( E , E )- 6a were formed for the oxygen derivative 6 , the selective formation of the desired diester ( Z , Z )- 7 was observed when employing the sulfur analogue (for details see below). This necessitated an alternative route to the target NON ligand, which is presented below.…”
Section: Resultsmentioning
confidence: 99%